I can be an astronomer - Sipiera, Paul P. (Chicago : Childrens Press, 1986)
Discusses the work that astronomers do as they study the stars to learn more about the universe.
Includes index.
Keywords: Astronomy -- Vocational guidance -- Juvenile literature; Astronomy -- Juvenile literature; Astronomy -- Vocational guidance; Vocational guidance; Occupations